2021
DOI: 10.1007/s00360-021-01359-9
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic tone benefits cardiac performance and warming tolerance in two teleost fishes that lack a coronary circulation

Abstract: Tolerance to acute environmental warming in fish is partly governed by the functional capacity of the heart to increase systemic oxygen delivery at high temperatures. However, cardiac function typically deteriorates at high temperatures, due to declining heart rate and an impaired capacity to maintain or increase cardiac stroke volume, which in turn has been attributed to a deterioration of the electrical conductivity of cardiac tissues and/or an impaired cardiac oxygen supply. While autonomic regulation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…The growth rates were positively correlated with the relative condition factor (K n ) in both cases. This is consistent with the assertion of [ 58 ] that higher K n values are indicative of fish wellness. High SGR and K n values observed in the control fish indicate that higher growth is associated with fish wellness.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The growth rates were positively correlated with the relative condition factor (K n ) in both cases. This is consistent with the assertion of [ 58 ] that higher K n values are indicative of fish wellness. High SGR and K n values observed in the control fish indicate that higher growth is associated with fish wellness.…”
Section: Discussionsupporting
confidence: 93%
“…Ref. [ 58 ] demonstrated that adrenergic activation enhances heart performance in acute thermal stress in various teleost.…”
Section: Discussionmentioning
confidence: 99%
“…This study did not examine the mechanisms responsible for the resetting of f H , but the increase in resting f H following acclimation to 1°C could have been the result of: a shift in cardiomyocyte membrane ion channel function and/or density ( Vornanen, 1998 ; Vornanen et al, 2002a , b ); an increase in adrenoreceptor sensitivity to extrinsic factors (i.e. circulating hormones adrenaline and noradrenaline) ( Gamperl and Farrell, 2004 ); and/or a change in the cholinergic and adrenergic control of cardiac function ( Ekström et al, 2016 , 2021 ; Porter et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Average ocean temperatures are predicted to rise by 2–4°C by the end of this century ( IPCC, 2018 , 2022 ), and this has prompted in-depth research over the past several decades to understand the impacts of high water temperatures on the physiology of fish (e.g. Andreassen et al, 2022 ; Ekström et al, 2021 ; Ørsted et al, 2022 ). However, marine environments are also experiencing extreme reductions in temperatures at an increased rate, and for prolonged periods of time.…”
Section: Introductionmentioning
confidence: 99%
“…This occurs by changing the heart rate (HR) more than the stroke volume [103,104]. When temperature acutely rises, the HR increases before declining at temperatures preceding the critical thermal maximum [103,104] and this compromises the cardiac function [102,105,106]. On the other hand, when the temperature drops, bradycardia occurs [107], and this is associated with an increased diastolic duration to maintain CO by increasing filling time and with little modifications of the systolic duration [108].…”
Section: Temperaturementioning
confidence: 99%